2014
DOI: 10.1158/2159-8290.cd-13-0897
|View full text |Cite
|
Sign up to set email alerts
|

miR-30c-2-3p and miR-30a-3p: New Pieces of the Jigsaw Puzzle in HIF2α Regulation

Abstract: Summary: Clear cell renal cell carcinoma (ccRCC), the most frequent subtype of renal cell cancer, is characterized by mutation of the von Hippel-Lindau ( VHL ) tumor suppressor gene, which results in stabilization of hypoxia-inducible factor (HIF) α proteins. In this issue of Cancer Discovery , Mathew and colleagues report that miR-30c-2-3p and miR-30a-3p downregulation in ccRCC promotes increased expression of HIF2α. Cancer Discov; 4(1);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We also showed that miR-196a-5p is up-regulated in LNM containing at least 70 % of tumor cells. In other cancers, miR-196a-5p and miR-30c-2-3p have also been respectively identified as up- [ 61 63 ] and down- [ 64 , 65 ] regulated during migration and invasion. So, although the microRNA expression profiles of primary tumors of PTC and LNM are very similar, some microRNAs are modulated and could participate to metastasis formation.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that miR-196a-5p is up-regulated in LNM containing at least 70 % of tumor cells. In other cancers, miR-196a-5p and miR-30c-2-3p have also been respectively identified as up- [ 61 63 ] and down- [ 64 , 65 ] regulated during migration and invasion. So, although the microRNA expression profiles of primary tumors of PTC and LNM are very similar, some microRNAs are modulated and could participate to metastasis formation.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization of HIF-1 and −2 through the loss of VHL is not the only factor contributing to the high levels of these transcription factors in RCC. Mathew et al have shown that RCC have low levels of the microRNAs miR-30-2-3p and miR-30a-3p compared to the normal renal parenchyma [31,32]. These microRNAs interfere with the translation of the HIF mRNAs and their absence from RCC cells allows for the HIF transcripts to be efficiently translated.…”
Section: Rcc Microvasculaturementioning
confidence: 99%
“…and HIF-2α can regulate miR-30a-3p expression negatively [29]. Then, we found loss of miR-30a-3p contributed to the progression of neuropathic pain.…”
Section: Discussionmentioning
confidence: 74%
“…In a mouse model of traumatic peripheral nerve injury, a persistent intimal hypoxia can cause neuralgia with elevated levels of HIF-1α [ 28 ]. HIF-1α and HIF-2α can regulate miR-30a-3p expression negatively [ 29 ]. Then, we found loss of miR-30a-3p contributed to the progression of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%